2019
DOI: 10.1042/bsr20193266
|View full text |Cite
|
Sign up to set email alerts
|

Koebner phenomenon leading to the formation of new psoriatic lesions: evidences and mechanisms

Abstract: Koebner phenomenon refers to the emergence of new psoriatic lesions in the healthy skin regions following an injury/trauma to psoriatic patients. The occurrence of psoriatic lesions at unusual areas of the body regions such as on penis, around eyes and on keloids suggest that the Koebner phenomenon may be responsible for these lesions. A number of agents/triggers have been reported to induce the development of new psoriatic lesions in healthy skin areas and these include, tattooing skin, radiations, skin incis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 104 publications
3
54
0
2
Order By: Relevance
“…Additionally, there were significantly higher H‐score mean values between psoriasis lesion and perilesional epidermis when compared to control groups. Our results agreed with previous studies which found that perilesional psoriatic skin is prone to develop psoriasis lesions which may explain koebnerization 24 …”
Section: Discussionsupporting
confidence: 93%
“…Additionally, there were significantly higher H‐score mean values between psoriasis lesion and perilesional epidermis when compared to control groups. Our results agreed with previous studies which found that perilesional psoriatic skin is prone to develop psoriasis lesions which may explain koebnerization 24 …”
Section: Discussionsupporting
confidence: 93%
“…The Köebner phenomenon after breast surgery is uncommon and generally associated with the occurrence of psoriatic lesions 2,7 ; however, there are descriptions of the phenomenon after radical mastectomy 8 , bilateral prophylactic mastectomy and reconstruction with prostheses 7 , and after skin-sparing mastectomy with immediate reconstruction, using prosthesis and latissimus dorsi muscle f lap 9 . To our knowledge, the cases reported in the current study are the first descriptions of this phenomenon after breast oncoplastic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology underlying the Köebner phenomenon remains inconclusive, despite the frequent observation of epidermal cell damage associated with the inflammatory dermal reaction 2,7 , but experimental studies involving its induction have shown divergent results when it comes to the clinical manifestations of the lesions 2 . Thus, physical, biochemical, and immunological factors can also be associated with the occurrence of the Köebner phenomenon and contribute to the diversity of clinical presentations seen in the literature 2,4,10 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations